Sistema de ecuaciones lineales con 2 variables - Herrera Santisteban, Armando (2019)
The Work of Professional Proficiency was entitled: System Linear equations with 2 variables whose development of the Learning Session, is based on the teaching of mathematics has made important the teaching and learning processes in different contents of the linear equations particularly in school situations, determining didactic conditions that allow improving teaching methods and content, ensuring that students evolve and can solve problems inside and outside the classroom. The third grade student learns to solve problems related to the relationships between very large or very small amounts, magnitudes or financial exchanges, translating them into numerical and operational expressions with rational or irrational numbers, scientific notation, intervals, and simple interest rates and compound. Evaluate whether these expressions meet the initial conditions of the problem. For the teaching of mathematics in students, individual and group work situations must be raised where in problems with numbers, they must use their knowledge and test their hypotheses, testing, discarding and retaking paths.